Optimal operation of combined cooling heat and power (CCHP) systems in future energy networks - Wang, Nianzu (2019)
Multiple energy resources will be integrated into the future energy networks for the purpose of supplying multi-energy loads and achieving maximum energy utilization efficiency. The energy included in this network cover fossil-fuel, wind, solar, nature gas, as well as other forms of energy such as heat and cooling, etc. An effective approach to enable the integration of multiply energy resources is the use of the combined cooling heat and power (CCHP) system. The research on optimal operation of the CCHP in a comprehensive energy network is the key of this report. Specific tasks include the modelling of the CCHP system and other energy resources that installed in a microgrid-based on the IEEE 33-bus network, as well as the optimization-based methodologies for operation of CCHP systems, the possible profit of selling energy to customers, comparison on the cost of supplying multi-energy load by separate generation and co-generation, etc.